Association of vitamin D and antioxidant enzyme levels in patients with delirium tremens: A case control study - Kamala Deka; Anju Moni Rabha; Mainak Roy (Industrial Psychiatry Journal)
Background: Global alcohol consumption poses a serious threat to humankind. It is estimated that between 5% and 7% of Indian adults struggle with alcohol abuse. Alcoholism is associated with a number of disorders, impacting different organ systems and nutritional status, including symptoms of withdrawal that can vary in severity from moderate symptoms to delirium tremens (DT). An increase in oxidative stress in the body is linked to alcohol withdrawal. Aim: This study aimed to evaluate the role of vitamins with antioxidant properties on oxidative stress caused by the severe alcohol withdrawal state. Materials and Methods: 60 patients with DT and 30 control subjects were recruited using a purposive sampling method. They were evaluated for liver function test, antioxidant enzyme superoxide dismutase, glutathione peroxidase, and serum vitamin D level on day 0, day 14 and on day 0 of treatment for patients and controls, respectively. Results: The mean age of the study group was 41.12 years. The mean duration of substance use while coming for treatment was 22 years. Means of liver function test were found to be aspartate transaminase (AST) 196 IU/L, alanine transaminase (ALT) 71 IU/L, and alkaline phosphatase (ALP) 143 IU/L of patients on day 0 of evaluation. When comparisons of liver enzymes and antioxidant enzymes were conducted between cases and controls on day 0, significance was found. Further comparison of day 0 and day 14 levels of liver enzymes and antioxidant enzymes also had shown significant differences. However, no significant correlation was found with vitamin D level and liver enzyme, antioxidant enzyme level. Conclusion: Oxidative stress evaluated via antioxidant enzyme was found to be at a higher level in patients with DT than in patients with mild withdrawal symptoms. This study has shown an association between antioxidant enzymes with severity of withdrawal; however, no such association with vitamin D level was found.